2009
DOI: 10.1007/s11205-009-9497-7
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in Human Development: An Empirical Assessment of 32 Countries

Abstract: One of the most frequent critiques of the HDI is that is does not take into account inequality within countries in its three dimensions. In this paper, we apply a simply approach to compute the three components and the overall HDI for quintiles of the income distribution. This allows a comparison of the level in human development of the poor with the level of the non-poor within countries, but also across countries. This is an application of the method presented in Grimm et al. (World Development 36(12):2527–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 7 publications
0
34
1
5
Order By: Relevance
“…Grimm et al (2010) applied a simply approach to compute the three components and the overall HDI for quintiles of the income distribution to make an empirical assessment of 32 countries and they found that a strong overall negative correlation between the level of human development and inequality in human development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Grimm et al (2010) applied a simply approach to compute the three components and the overall HDI for quintiles of the income distribution to make an empirical assessment of 32 countries and they found that a strong overall negative correlation between the level of human development and inequality in human development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aguña and Kovacevic (2010) divided the economy into four clusters according to the HDI categorization by the United Nations. Grimm et al (2010) used a hierarchical cluster analysis of 32 countries with respect to the inequality in the three components of HDI. Ülengin et al (2009) or Rende and Donduran (2011) used the Self-organizing Maps for the creation of clusters.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand one can explore the distribution of improvements as is, o¤ering the possibility to researchers and policy-makers of investigating local level improvement patterns and their relationship with key socio-economic or demographic variables. This approach is conceptually related to recent attempts of constructing subgroup speci…c versions of welfare indices that were originally de…ned at the country level (as is the case with the Human Development Index, which has been rede…ned for income quintiles, migrants and non-migrants, households or di¤erent administrative units; see Grimm, Harttgen, Klasen and Misselhorn 2008, Grimm et al 2010, Harttgen and Klasen 2011a, 2011b, Permanyer 2013. On the other hand, one might attempt to summarize that wealth of information into an overall improvement index that takes into account certain characteristics of the underlying distribution (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As is done in recent studies in the context of human development measurement (see Grimm, Harttgen, Klasen and Misselhorn 2008, Grimm et al 2010, Harttgen and Klasen 2011a, 2011b, Permanyer 2013, the improvements distribution can be left as is to guide researchers and policy-makers about local patterns of improvement, inform about the extent of inequality and give clues to understand why underdevelopment prevails in certain areas and what perpetuates it. An illustration of this approach is shown in section 4.…”
Section: The Multi-individual Case: Introducing Heterogeneitymentioning
confidence: 99%